2021
DOI: 10.1371/journal.pone.0244937
|View full text |Cite
|
Sign up to set email alerts
|

Covert cases of Severe Acute Respiratory Syndrome Coronavirus 2: An obscure but present danger in regions endemic for Dengue and Chikungunya viruses

Abstract: Background The impact of SARS-CoV-2 in regions endemic for both Dengue and Chikungunya is still not fully understood. Considering that symptoms/clinical features displayed during Dengue, Chikungunya and SARS-CoV-2 acute infections are similar, undiagnosed cases of SARS-CoV-2 in co-endemic areas may be more prevalent than expected. This study was conducted to assess the prevalence of covert cases of SARS-CoV-2 among samples from patients with clinical symptoms compatible with either Dengue or Chikungunya viral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 26 publications
1
22
0
2
Order By: Relevance
“…Furthermore, reports have suggested that subclinical cases with mild or no symptoms could act as reservoirs, spreading the virus unknowingly across the population cohort and thus making the situation even worse. Evidences have suggested that covert cases pose a serious threat in compliance of public health mitigation strategies, creating great difficulties in combating the disease[ 4 ]. Although 2019-nCoV patients show resemblance in symptoms to the MERS-CoV (Middle East respiratory syndrome-CoV) and SARS-CoV (Severe acute respiratory syndrome-CoV) infections, pathophysiology of 2019-nCoV infection and exact molecular mechanism behind the unusually high virulence and infectivity of SARS-CoV-2 is not clearly understood yet.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, reports have suggested that subclinical cases with mild or no symptoms could act as reservoirs, spreading the virus unknowingly across the population cohort and thus making the situation even worse. Evidences have suggested that covert cases pose a serious threat in compliance of public health mitigation strategies, creating great difficulties in combating the disease[ 4 ]. Although 2019-nCoV patients show resemblance in symptoms to the MERS-CoV (Middle East respiratory syndrome-CoV) and SARS-CoV (Severe acute respiratory syndrome-CoV) infections, pathophysiology of 2019-nCoV infection and exact molecular mechanism behind the unusually high virulence and infectivity of SARS-CoV-2 is not clearly understood yet.…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have shown that serology for COVID-19 can exhibit cross-reactivity with dengue even when protein S is used 17 , 18 . On the other hand, in the initial phase of both diseases, in which viremia peaks, the RT-PCR diagnostic tests for COVID-19 and the NS1 detection for dengue diagnosis have been identified as tools with good discriminatory capacity between these diseases 19 , 20 .…”
Section: Discussionmentioning
confidence: 99%
“…In a study that analyzed samples of 7,370 patients, without prior suspicion of COVID-19, but who had symptoms compatible with viral infections such as Dengue or Chikungunya, from December 1, 2019, to June 30, 2020, the results illustrated that 210 SARS-CoV-2 positive cases were detected. These hidden cases possibly indicate delays in seeing patients, which may have contributed to the rapid expansion of the COVID-19 outbreak 29 .…”
Section: Discussionmentioning
confidence: 99%